Revisiting the relationship of dynamic and resilient modulus test for asphaltic concrete mixtures. (10th May 2018) - Ali, Yasir; Irfan, Muhammad; Zeeshan, Muhammad; Hafeez, Imran; Ahmed, Shafeeq
Highlights: A correlation of |E ∗ | and MR is developed. Developed correlation is rigorously tested and is compared with an existing correlation. A statistical model for predicting |E ∗ | as function of MR, gradation and mix volumetric parameter is presented. Abstract: Mechanistic-Empirical Pavement Design is considered relatively more effective than conventional empirical design for excessive tyre pressure exerted by axle load spectra and diverse environmental conditions. Many highway agencies are adopting a paradigm shift to Mechanistic-Empirical pavement design practices, obsoleting huge inventories of resilient modulus database used for empirical design. This paper attempts to develop an empirical correlation of dynamic modulus (|E ∗ |) and resilient modulus (MR ) – two performance tests used to characterize the stiffness of asphaltic concrete mixtures, and proposes a statistical model for |E ∗ | as a function of MR, gradation parameter, and mix volumetric parameter. For the comparison purpose, a rigorous testing using bi-level testing protocol is offered for all the relationships (i.e., correlation and model). The comparison of |E ∗ | with MR shows that at a temperature of 25 °C, |E ∗ | at 5 Hz is strongly correlated with MR at a loading frequency of 300 ms. The developed statistical model captured 97% of the variability in the data in predicting |E ∗ | from MR with an error of 6% and 23% for first and second level of bi-level testing protocol, respectively. It is envisaged that the findings of this study can help the highway agencies and practitioners in smooth transitioning to Mechanistic-empirical pavement design practices.